Management Strategy of Sub-Watersheds Affected By Flooding In Banjar District, South of Kalimantan - Safa Muzdalifah; Farah Qubayla; Said Khaidir (International Journal of Politic, Public Policy and Environmental Issues, 2021)
Watershed Management is the process of formulating and implementing a series of activities involving natural and human resources in a watershed, taking into account social, political, economic, and institutional factors in the watershed and surrounding areas to achieve specific social goals. This study analyzes the local government's strategy in managing the affected sub-watersheds (DAS) flood- in Banjar Regency, South Kalimantan. The background of the research is the occurrence of floods in the sub-watershed in Banjar Regency. In a follow-up review, the provincial government has the authority to manage watersheds within the province. On the power of the government, and the existing conditions, an in-depth analysis of the local government's strategy in managing the sub-watershed in Banjar Regency is needed. To answer the research problem, a descriptive qualitative research method was used. The location of this research is in Banjar Regency. The key informants of the research are elements of the South Kalimantan provincial government, especially those authorized in the management of the Martapura Sub-watershed, namely the Kayu Tangi Forest Management Unit (KPH) Organization and the Head of the South Kalimantan Province Environmental Service. This study indicates that local governments in carrying out local government strategies in managing flood-affected watersheds apply reforestation strategies, and the construction of a dam, namely Riam Kanan Dam, and still in planning is the construction of Riam Kiwa Dam. The watershed management strategy has not been maximized in flood prevention because the Riam Kiwa Dam program and waterway maintenance have not been realized.